Guidelines for PMR Favor Lowest Effective Dose of GCs as Initial Therapy - Kuznar, Wayne (MD Conference Express, 2014)
The 2014 American College of Rheumatology/European League Against Rheumatism guidelines proposal for the treatment and management of polymyalgia rheumatica and the process to develop them are discussed in this article.